Blind outcome assessment: the development and use of procedures to maintain and describe blinding in a pragmatic physiotherapy rehabilitation trial. - Minns Lowe, C; Wilson, MS; Sackley, C; Barker, K (2011)
OBJECTIVES: (1) To develop trial protocols which promote the achievement of blind outcome assessment. (2) To report outcome assessor beliefs regarding group allocation at follow-up assessments. (3) To document and describe instances of unblinding occurring during the trial to assist and inform rehabilitation researchers and clinicians. DESIGN: Prospective longitudinal observational study. SETTING: An NHS Hospital Trust specializing in orthopaedic surgery. SUBJECTS: One hundred and seven patients participating in a prospective pragmatic randomized controlled trial investigating physiotherapy rehabilitation following total knee arthroplasty, plus three outcome assessors. INTERVENTIONS: A protocol was developed using available research and designed to minimize instances of unblinding during a physiotherapy rehabilitation trial. Administrative, office, patient and research staff procedures were included. MAIN MEASURES: Trial questionnaires measured blind outcome assessment responses at 3 and 12 months post surgery. The outcome assessor kept a field diary recording the events surrounding instances of unblinding. Data underwent descriptive and content analysis. RESULTS: Blind outcome assessment was believed successful for n = 74 (81.32%) assessments at 3-month follow-up, and n = 83 (91.21%) at 12 months. Forty instances (n = 28 participants) of unblinding were described in the field diary. While the main cause of unblinding was participants telling the outcome assessor, in 12.5% of events the assessor drew the wrong conclusion regarding group allocation. Not all unblinding events were remembered at subsequent assessments, even in this relatively small trial. CONCLUSIONS: Blind outcome assessment was considered achievable in this trial. Specific trial protocols enabled blinding beliefs to be reported and instances of unblinding to be described.